Proposta de calendário de eventos turísticos - Lima, Lindyneuza Cavalcante de (2019)
Event Calendar is an important marketing tool for event promotion and should be used by both public management and private enterprise. Nowadays, with the use of digital technology and social networks, the calendar of events presents itself as an effective way of dissemination and communication, allowing the target audience to access information about the events, the locality and its services and attractions, making it It is also a tourist promotion tool. Thus, the objective of this work was to present a proposal of Calendar of Tourist Events, in digital platform, in order to meet the demands of public management of the municipalities of the state of Rio Grande do Norte and contribute to the dissemination and promotion of events and tourism. in the state. The research, therefore, is applied in nature, with a qualitative approach, having been based on theoretical knowledge about event tourism, communication and calendar of events, directed to the practical application focused on the specific problem solving outlined by the research. Finally, the present work makes available a digital tool, open to public sector managers, for the cataloging and creation of Municipal Calendars of Tourist Events.